การประเมินหลักสูตรจินตคณิต ของสถาบัน 072 จินตคณิต โดยใช้ CIPPIEST MODEL - ชาดง สุปัญญา; จงกลกลาง สิรินาถ (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2019)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อประเมินหลักสูตรจินตคณิต ของสถาบัน 072 จินตคณิต โดยใช้ CIPPIEST Modelด้านบริบท ด้านปัจจัยเบื้องต้น ด้านกระบวนการ และด้านผลผลิต กลุ่มตัวอย่างในการวิจัย คือ ผู้เกี่ยวข้องกับหลักสูตร จินตคณิต สถาบัน 072 จินตคณิต ประจำปี 2560 จำแนกเป็น ผู้บริหาร จำนวน 31 คน ครูผู้สอน จำนวน 31 คน และผู้ปกครองนักเรียน จำนวน 72 คน ได้มาโดยการเลือกแบบแบ่งชั้นอย่างเป็นสัดส่วน กลุ่มตัวอย่างที่ใช้ในการสัมภาษณ์ได้มาโดยการสุ่มอย่างง่าย ได้แก่ ผู้บริหาร ครูผู้สอน และผู้ปกครองนักเรียน กลุ่มละ 10 คน รวม 30 คน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล ได้แก่ แบบสอบถามความคิดเห็นเกี่ยวกับหลักสูตรจินตคณิต และแบบสัมภาษณ์ จากนั้น นำข้อมูลมาวิเคราะห์หาค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และวิเคราะห์เนื้อหา ผลการวิจัย พบว่าความคิดเห็นเกี่ยวกับหลักสูตรจินตคณิตของผู้บริหาร ครูผู้สอน และผู้ปกครอง ด้านบริบท ด้านปัจจัยเบื้องต้น ด้านกระบวนการ และด้านผลผลิต ซึ่งประกอบด้วยการประเมินผลกระทบ ประสิทธิผล ความยั่งยืน และการถ่ายทอดส่งต่อ อยู่ในระดับมาก และผ่านเกณฑ์ การประเมิน คำสำคัญ : ประเมินหลักสูตร รูปแบบการประเมิน CIPPIEST จินตคณิต ABSTRACT The purpose of this study was to evaluate Mental Arithmetic curriculum of 072 JintakanitInstitue by using CIPPIEST model. The evaluation model applied for this study consists of 4 aspects: context evaluation, input evaluation, process evaluation and product evaluation. The research samples consist of related people with the Mental Arithmetic curriculum of 072 Jintakanit Institute 2017, including 31 executives, 31 teachers and 72 parents. The samples were obtained by choosing a stratified proportion. Besides, the samples used in the interview were obtained by simple random sampling, including 3 groups of executives, teachers, and parents. Each group consists of 10 people, a total of 30 people. The research tools used for data collection include questionnaire about the Mental Arithmetic curriculum in interview type. The collected data then were analyzed for percentage (%) ,mean () ,standard deviation (S.D)., and content analysis. The results of the research found that the opinions about the Mental Arithmetic curriculum of executives, teachers and parents in the context evaluation, input evaluation, process evaluation and product evaluation, which consist of impact evaluation, effectiveness evaluation, sustainability evaluation and transferability evaluation. The opinions were at a high level and passed the evaluation criteria. Keywords: Evaluation Curriculum, CIPPIEST Evaluation Model, Mental Arithmetic